(untitled) (Global Journal of Science Frontier Research, 2012)
Effective Micro-organism (EM) is a product characterized by a mix of aerobic and anaerobic microorganisms and reported to have successfully be used for increasing productivity in integrated animal units and poultry farms in many countries including South Africa. The objective of this study was to evaluate the effect of EM on the production performance of Rhode Island Red (RIR) chicks. A total of 348 RIR day old chicks were randomly divided into twelve groups of 29 chicks each and each group was housed in separate individual pen thoroughly cleaned and prepared in advance. Finally 4 treatments containing 0, 4, 8 and 12 ml of EM/litre of drinking water were randomly assigned to the experimental chicks in completely randomized design with 3 replicates for study period of 12 weeks. Feed consumption, chick growth, feed conversion efficiency and survival rate were used as evaluation parameters. The results showed that there was no significant difference between all the treatment groups (P>0.05) in mean weekly feed consumption though the groups placed on the treatment containing 0 ml/liter of water tended to consume more.